PSIKOEDUKASI PENYAKIT MENULAR SEKSUAL HIV/AIDS PADA REMAJA AWAL - Rizki Nur Pratama (Prosiding Seminar Kesehatan Nasional Sexophone, 2023)
AbstractEarly adolescence is a developmental period in which individuals experience many changes and upheavals. In the transition, adolescents have the task of accepting and understanding the role of the adult sex, and if adolescents are not educated about their age roles, it is feared that they will cause various problems. HIV/AIDS, as a dangerous sexually transmitted disease, can infect anyone, especially teenagers who are experiencing developmental turmoil. A psychoeducational approach with the theme of HIV/AIDS sexually transmitted diseases is the right step for students who are just entering their early teens at MI Thoriqul Huda. This method in psychoeducation uses a lecture, discussion, and question-and-answer approach between presenters and participants, as well as measuring results to evaluate the program's success. In general, this activity received a positive response. The evaluation results showed an increase in participants knowledge of HIV/AIDS sexually transmitted disease psychoeducation (mean 10) with a total of 16 participants. The implication of psychoeducation that it is hoped that grade 6 students at MI Thoriqul Huda will be able to become agents of change in an environment free of HIV/AIDS, suggestions for further psychoeducational activities to carry out psychoeducation of other sexually transmitted diseases considering that the types of sexually transmitted diseases are very diverse.Keywords: Early Adolescence; Psychoeducation; Sexually Transmitted InfectionAbstrakMasa remaja awal merupakan periode perkembangan di mana individu mengalami banyak perubahan dan gejolak. Dalam transisinya, remaja memiliki tugas dalam menerima dan memahami peran seks usia dewasa, apabila remaja kurang teredukasi akan peran usianya dikhawatirkan akan menimbulkan berbagai permasalahan. HIV/AIDS sebagai salah satu penyakit menular seksual yang berbahaya dapat menyerang siapa saja, terutama remaja yang sedang mengalami gejolak perkembangan. Pendekatan psikoedukasi dengan tema penyakit menular seksual HIV/AIDS menjadi langkah tepat, bagi siswa-siswi yang baru memasuki fase remaja awal di MI Thoriqul Huda. Psikoedukasi ini menggunakan metetode ceramah, diskusi, dan tanya jawab antara pemateri dengan para peserta, serta mengukur hasil untuk mengevaluasi keberhasilan program. Secara keseluruhan, kegiatan ini mendapatkan respon positif. Hasil evaluasi menunjukkan bahwa terdapat peningkatan pengetahuan partisipan dalam psikoedukasi penyakit menular seksual HIV/AIDS (mean 10) dengan jumlah partisipan 16 orang. Implikasi dari kegiatan ini diharapkan siswa-siswi kelas 6 di MI Thoriqul Huda mampu menjadi agen perubahan dengan lingkungan yang bebas HIV/AIDS, saran untuk kegiatan psikoedukasi selanjutnya untuk dilaksanakan psikoedukasi penyakit menular seksual lainnya mengingat jenis penyakit menular seksual sangat beragam.Kata kunci: Remaja Awal; Psikoedukasi; Penyakit Menular Seksual